2012
DOI: 10.1155/2012/512926
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Src Kinase in Macrophage-Mediated Inflammatory Responses

Abstract: Src kinase (Src) is a tyrosine protein kinase that regulates cellular metabolism, survival, and proliferation. Many studies have shown that Src plays multiple roles in macrophage-mediated innate immunity, such as phagocytosis, the production of inflammatory cytokines/mediators, and the induction of cellular migration, which strongly implies that Src plays a pivotal role in the functional activation of macrophages. Macrophages are involved in a variety of immune responses and in inflammatory diseases including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
195
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(211 citation statements)
references
References 157 publications
8
195
0
1
Order By: Relevance
“…On examining candidate kinase pathways, the metabolic effect of oxLDL was completely abrogated by an Src inhibitor (PP2), a critical player in the functional activation of macrophages (28), as well as by a PI3K inhibitor (LY-294002), consistent with the regulatory role of this pathway in glucose metabolism and immune cell activation (29).…”
Section: Discussionmentioning
confidence: 84%
“…On examining candidate kinase pathways, the metabolic effect of oxLDL was completely abrogated by an Src inhibitor (PP2), a critical player in the functional activation of macrophages (28), as well as by a PI3K inhibitor (LY-294002), consistent with the regulatory role of this pathway in glucose metabolism and immune cell activation (29).…”
Section: Discussionmentioning
confidence: 84%
“…SRC is a proto-oncogene encoding a non-receptor tyrosine kinase, similar to the v-Src gene of the Rous sarcoma virus (14), which was initially discovered by Bishop and Varmus (15). The Src protein is formed of seven functional regions: i) N-terminal Src homology domain 4 (SH4) containing a myristic acid moiety, essential for its localization to the inner surface of the cell membrane; ii) a unique domain providing functional specificity to each member of the Src family; iii) SH3 domain, which binds proline-rich sequences to mediate intra-and intermolecular interactions; iv) SH2 domain, which binds phosphorylated tyrosine residues on Src and other proteins; v) a catalytic domain (SH1); and vi) C-terminal tail containing negative-regulatory Tyr530 (in humans) (16)(17)(18) (Fig.…”
Section: Srcmentioning
confidence: 99%
“…5) revealed that the Bd-EE extract was able to directly suppress Syk and Src, which are important protein tyrosine kinases in the NF-κB pathway (Johnson, Li, & Pearlman, 2008). According to several studies, Src and Syk play varied roles in macrophage-mediated innate immunity, including immune cell cycle, phagocytosis, the production of inflammatory cytokines/mediators, and gene expression (Byeon et al, 2012;Frommhold et al, 2007;Yi et al, 2014). Alternatively, collaboration of the Syk and TLR4/MyD88 pathways results in the sustained degradation of IκBα, enhancing NF-κB nuclear translocation, resulting in the control of infectious materials ( Lee et al, 2009;Yi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%